'If he sees it with his own eyes, he will understand': how gender informed the content and delivery of a maternal nutrition intervention in Burkina Faso. Issue 5 (27th February 2020) - Isler, Jasmin; Sawadogo, N Hélène; Harling, Guy; Bärnighausen, Till; Adam, Maya; Sié, Ali; McMahon, Shannon A
Abstract: A growing body of literature urges policymakers, practitioners and scientists to consider gender in the design and evaluation of health interventions. We report findings from formative research to develop and refine an mHealth maternal nutrition intervention in Nouna, Burkina Faso, one of the world's most resource-poor settings. Gender was not an initial research focus, but emerged as highly salient during data collection, and thus guided lines of inquiry as the study progressed. We collected data in two stages, first using focus group discussions (FGD; n  = 8) and later using FGDs ( n  = 2), interviews ( n  = 30) and observations of intervention delivery ( n  = 30). Respondents included pregnant women, breastfeeding mothers and Close-to-Community (CTC) providers, who execute preventative and curative tasks at the community level. We applied Morgan et al. 's gender framework to examine intervention content (what a gender-sensitive nutrition programme should entail) and delivery (how a gender-sensitive programme should be administered). Mothers emphasized that although they are often the focus of nutrition interventions, they are not empowered to make nutrition-based decisions that incur costs. They do, however, wield some control over nutrition-related tasks such as farming and cooking. Mothers described how difficult it is to consider only one's own children during meal preparation (which is communal), and all respondents described how nutrition-related requests can spark marital strife. Many respondents agreed that involving men in nutrition interventions is vital, despite men's perceived disinterest. CTC providers and others described how social norms and gender roles underpin perceptions of CTC providers and dictate with whom they can speak within homes. Mothers often prefer female CTC providers, but these health workers require spousal permission to work and need to balance professional and domestic demands. We recommend involving male partners in maternal nutrition interventions and engaging and supporting a broader cadre of female CTC providers in Burkina Faso.